Analysis of Organizational Capacity Development National Food Agency - Doddy Heryadi; Vishnu Juwono (Asian Journal of Social and Humanities, 2024)
National food security is the nation's main capital in realizing prosperity and increasing competitiveness and facing global challenges. In response to these conditions, the Government has taken a number of steps to improve national food management, one of which is through Law No. 18 of 2012 regarding Food and its derivative regulations which mandate the formation of a National Food Agency. Nearly three years after its formation, the performance of the National Food Agency still has a number of obstacles in terms of limited infrastructure, limited budget, limited human resources, and performance indicators that are not in accordance with the authority of the Agency. The article entitled Analysis of Organizational Capacity Development of the National Food Agency aims to analyze the development of the organizational capacity of the National Food Agency so that it is able to carry out its duties and functions optimally through the concept of organizational capacity development theory. Data collection in this research used a qualitative approach through analysis of literature studies from journals, books and statutory regulations documents as well as making observations, then comparing the results of the literature study collection and observations. Based on the analysis that has been carried out, the organizational capacity of the National Food Agency needs to be increased through development in the dimensions of staffing, human resources , resource development, financial health, and financial systems, and strategic planning, mission, and vision.